Model-based financial regulation challenges for the net-zero transition - Gasparini, M; Ives, M; Carr, B; Fry, S; Beinhocker, E (Springer Nature, 2024)
The current structure of some existing model-based financial regulations implicitly favours investment in carbon-intensive activities, working against broader government and societal objectives of transitioning to net-zero carbon emissions. Structured as they are, such financial regulations may exacerbate climate-related risks in the financial system, thereby working against one of the primary objectives of financial supervisors, which is to preserve financial stability. Legislators and governmental agencies should be aware that this implicit bias may lead to a misalignment between the financial system’s allocation of capital and the use of fiscal and other policy tools by governments to crowd-in private capital to finance the energy transition, thus undermining the effectiveness of those policies. Financial supervisors, regulators and international standard-setting bodies (for example, the International Sustainability Standards Board and the Financial Stability Board) should consider addressing these issues within the existing standards and regulatory framework, including using more forward-looking risk assessments, such as scenario analysis, and other macroprudential tools.